ANALISIS PENERIMAAN PAJAK KENDARAAN BERMOTOR (PKB) DI KOTA PALU - Putra, Anggy (Fakultas Ekonomi Universitas Tadulako, 2017)
This study determines the growth, effectiveness, efficiency, and contribution of motor vehicle tax revenue in Palu City. Based on the results for over 5 years from 2011 to 2015, the growth of taxes on motor vehicles increases annually but in percentage is fluctuated with 13.39% of achievement in average. This is due to the lack of public awareness and cooperation of government about the importance of the tax. However, the effectiveness of the motor vehicle tax in Palu is very effective with the average percentage of 109.17%. This achievement is supported by good supervision and control towards the motor vehicle tax collection in Palu. The level of efficiency of the motor vehicle tax in Palu is categorized efficient. This is caused by the amount of collection only 5%; the implementation of motor vehicle tax efficiency in Palu by the government especially by UPTD Palu and contribution rate of motor vehicle taxes in Palu show good growth.